Integration of Artificial Intelligence and Macro-Economic Analysis: A Novel Approach with Distributed Information Systems - Al Ahmad, Ana Shohibul Manshur; Judijanto, Loso; Tooy, Dedie; Putra, Purnama; Hermansyah, Muhammad; Kumalasanti, Maria; Agit, Alamsyah (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: This study introduces a groundbreaking approach that integrates Artificial Intelligence (AI) with macro-economic analysis to address a critical gap in existing economic forecasting methodologies. By leveraging diverse economic data sources, the study aims to transcend traditional analytical boundaries and provide a more comprehensive understanding of macroeconomic trends. OBJECTIVE: The primary objective is to pioneer a scalable framework for economic data analysis by combining AI with macroeconomic analysis. The study aims to utilize advanced machine learning algorithms to analyze and synthesize macroeconomic indicators, offering enhanced accuracy and predictive power. A key focus is on dynamically incorporating real-time data to adapt to evolving economic landscapes. METHODS: The research employs advanced machine learning algorithms to analyze and synthesize macroeconomic indicators. The integration of AI allows for a more nuanced understanding of complex economic dynamics. The methodology uniquely adapts to real-time data, providing a scalable framework for economic data analysis. RESULTS: The findings demonstrate the model’s efficacy in predicting economic trends, surpassing conventional models in both precision and reliability. The study showcases the potential of AI-driven economic analysis to offer insights into economic dynamics with unprecedented accuracy. CONCLUSION: This study significantly contributes to the fields of AI and economics by proposing a transformative approach to macroeconomic analysis. The integration of technology and economics sets a new precedent, paving the way for future innovations in economic forecasting. The research also explores the implications of AI-driven economic analysis for policy-making, emphasizing its potential to inform more effective economic strategies.